Between a Calling and Economic Reality: A Phenomenological Study of Honorary Teachers’ Motivation in Developing Competence - Muhtadin Muhtadin (Green Publisher Indonesia, 2026)
This study examines the phenomenon of honorary teachers’ motivation in developing professional competence within the tension between a sense of calling and economic reality in the Indonesian educational context. Using a qualitative phenomenological approach, the research explores the lived experiences and subjective meanings constructed by honorary teachers as they navigate economic uncertainty and limited access to professional development. Data were collected through in-depth interviews and participatory observations involving ten honorary teachers who graduated within the last five years and work in urban areas, and were analyzed using thematic analysis. The findings reveal four major themes: teaching as a calling that provides intrinsic meaning, economic pressure and job insecurity that generate identity conflict, adaptive strategies employed to sustain professional competence development, and social support as a crucial source of motivation. These results highlight the complex interaction between intrinsic and extrinsic motivation within conditions of social marginalization and emphasize the role of structural and social support in sustaining honorary teachers’ professional commitment. The study contributes theoretically by extending motivation theory through the inclusion of existential dimensions and social capital, and practically by offering policy-relevant insights for designing more inclusive and responsive professional development and welfare programs for honorary teachers. Overall, this research underscores the importance of understanding teachers’ lived experiences to promote equitable and sustainable educational development.